Some Ghanaian herbal blood tonics as sources of Iron and other trace elements(Cu, Zn, Mn, Cd, Pb) (Journal of Science and Technology, 2016)
Iron deficiency anaemia constitutes about 80 percent of all anaemia cases in developing countries. In Ghana, the 2003 Demographic and Health Survey reported anaemia prevalence of 67% for urbanresidents. Anaemia and loss of appetite are the common indications included in the consumer information on the labels on bottles of the numerous Ghanaian herbal blood tonics sold in retail pharmacyand chemical shops. In this study, ten brands of commonly advertised herbal blood tonics on the Ghanaian market were assessed for the levels of iron and other trace elements, wavelength of maximum absorption (ëmax), pH, salinity and total dissolved solids (TDS). These physico-chemical parameters were determined using a UNICAM 929 atomic absorption spectrophotometer, CECIL 8000 uv-visible spectrophotometer, JENWAY 3020 pH meter and LF538 conductivity meter. Maximum estimated daily dosages of less than 1 mg/day of iron was obtained for all the herbal tonics, except the Madam Catherine brand which had 2.17 mg, compared with the required daily intake of10 – 15 mg. The tonics also appear to be poor sources of the essential metals determined. Cd was detected in Adutwumwaa, Madam Catherine and Top tonics, while Pb was detected in Amingya iron tonic and Madam Catherine; but the levels of these toxic metals will not exceed the recommended safety standards, if the manufacturer’s dosages are adhered to.